معـاني القـول وأثرهـا في الحكم النحـوي في كتـاب معـاني القـرآن للفراء ت ٢07هـ : جمعًا ودراسة - Al-Sarhani | السرحاني, Ali Yahya Muhammad | علي يحيى محمد (2023)
This is a research entitled Meanings of Saying, and I see it in the grammatical ruling in the book “The Meanings of the Qur’an for Al-Fara’” (d. 207 AH), collected and studied. The research consists of an introduction, a preface, four sections, a conclusion and technical indexes. His idea is based on explaining the impact of the things that contain the meaning of the saying of supplication, the call, the writing, the will and the like on many grammatical rulings related to vocabulary and structures, and do they take the provisions of the saying or not? Al-Far’ meant in Mutabah the Meanings of the Qur’an by highlighting this idea in his book, and this study had an impact on the provisions of vocabulary, structures, different styles, interpretation, and grammatical reasoning. his opinions. | هذا بحث بعنوان معاني القول , وأرها في الحكم النحوي في كتاب معاني القرآن للفراء (ت207ه) جمعا و دراسة. يتكون البحث من مقدمة وتمهيد و أربعة مباحث و خاتمة و فهارس فنية. و تقوم فكرته على بيان أثر الأشياء التي فيها معنى القول من الدعاء, و النداء , و الكتابة , والوصية و نحوها في كثير من الأحكام النحوية المتعلقة بالمفردات والتراكيب, وهل تأخذ احكام القول او لا ؟ وقد عني الفراء في متابه معاني القرآن بإبراز هذه الفكرة في كتابه, و لهذه الدراسة أثر في أحكام المفردات و التراكيب و اختلاف الأساليب , و التأويل, و التعليل النحوي و قامت الدراسة على ايراد أقوال العلماء ممن وافق الفراء او خالفه, و مناقشة الفراء في بعض آرائه.